Biomechanical Evaluation of Flexor Tendon Repair: Double Loop Technique with Epitendinous Suture - Sadagatullah AN; Raghu S; Paiman M; Ismail S; Jusoh MH (Malaysian Orthopaedic Journal)
Introduction: There are various methods used to repair lacerated tendons. The minimum requirement for the best results and lowest rupture rate is the four-strand repair technique. The cruciate type of repair is among the most popular methods available but is very technical and requires expertise. An easier two-double-loop method for tendon healing is suggested in this study. This study assessed the biomechanical properties of two well-known tendon repair techniques—the modified Kessler and cruciate approaches—and two lesser-known double-loop techniques for tensile strength, stiffness, and failure mode. Materials and methods: Twenty-four adult chickens' Achilles tendons were randomly divided into three groups and sutured with a four-strand core suture using the four-strand modified Kessler technique, the four-strand cruciate technique, and the two-double-loop approach. Twenty-four more adult chicken Achilles tendons were acquired, and they were randomly assigned to the same three groups along with an extra running epitendinous repair. A synthetic, non-absorbable monofilament polypropylene suture was used for all repairs. Results: The four-strand modified Kessler, and the four-strand cruciate procedures had the lowest mean ultimate tensile strength, whereas the two double-loop techniques had the strongest. The results were dramatically impacted by using an epitendinous suture during test analysis. Conclusion: The strongest and comparatively less technically complex technique used in this investigation was the two-double-loop, four-strand core suture method. The significance of the extra strength that the epitendinous suture gave was clear. Using this in a clinical setting is recommended for hand flexor tendon injuries.